أثر أدوات السياسة المالية في النمو الاقتصادي في الاقتصاد السعودي والاقتصاد الأردني للمدة 1970-2003 - د. أحمد حسين الهيتي; د. فاطمة ابراهيم خلف (PROSPECTIVE RESEARCHES, 2023)
The relation between the financial policy and the economic development is considered as one of the subjects that was paid a great deal of attention by the economic and financial studies, and took different forms and dimensions as the subject is dealt with. In this research many financial indicators were used to study and analyze the relation between the financial policy and development, and the extent of effect between the two variables. The common feature of most of the studies that the research depended on refers the fact that this relation can extend from financial policy to development, and visa versa. The matter which gives the chance to causal relations between financial policy and economic development to appear. The study hypothesizes. That the economic development attraction of financial policy gives a strong likelihood for multiplicity of causal relation between the first and the second, in addition to the difference of the effect from one country to another. The researcher has found that the increase of total returns in Saudi Arabian economy with a percentage of 1% causes to increase the governmental spending with a percentage of 0.0005 to a thousand, while the reduction of economic development rate with a percentage of 1% causes to reduce the governmental spending with a percentage of 0.27%. And the reduction in the deficit with a percentage of 1% causes the increase of governmental spending with a percentage of 17.41%. As for Jordan, there is a causal relation between the total returns and governmental spending, which means that the increase of total returns causes the increase of governmental spending, in addition, the total returns depend mainly on governmental returns, and the increase of governmental spending on (health care and improving population's life) can activate the rates of development in the total economy. The researcher proposes that Saudi Arabia needs to treat the defect resulting from depending on earnings income resources in funding the public spending, and the necessity of researching and balancing income resources resulting from taxes earnings and financial funding. As for Jordan, we propose to direct towards financial and taxes reformation, variability of taxes income resources, treating deficiency in the regulations concerning taxes avoidance as an attempt to increase the financial outcome of the state accompanied by achieving economic and social aims of financial and taxes policies.